(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Puesto Viejo Group is a minor Triassic con- tinental unit located in the San Rafael Block (Fig. 1), in the Mendoza Province, Argentina (34º70’ S and 68º20’ W), to the west of the main Triassic accumulations of the Cuyo Basin (Ramos, 1993). The NNW-SSE disposition of the basin copy the strike of the inherited Paleozoic orogenic history of the San Rafael Block (San Rafael Orogeny; Kleiman and Japas, 2009). The knowledge of the Puesto Viejo Group is based on regional, sedimentological and biostratigraphic studies. Radiometric ages estimated from ignimbrites and basalts of the Puesto Viejo Group (232±10 My, Valencio et al., 1975; 245 My, Domeier et al., 2011; 235.8±2 My, Ottone et al., 2014), placed its development from the Middle to Upper Triassic, under the extensional regime linked to the Huárpica phase. This data allow integrating the Puesto Viejo Group into the general geochronological context of the Triassic extension of western Argentina (Ottone et al., 2014), with a main rift stage that evolved during the Middle Triassic. The sedimentary and volcanic infill of the Puesto Viejo Group consists of up to 1000 meters of alluvial and fluvial continental deposits with products of a bimodal magmatism in the form of rhyolitic pyroclastic flows, andesitic lavas and shallow intrusives (González Díaz, 1964; Spalletti, 1994; Kokogián et al., 1999, 2001; Kleiman and Salvarredi, 2001; Sepúlveda et al., 2007). It was deposited in different structural depressions boun- ded by normal faults (Fig. 2). Three levels of volca- nic rocks were used as geochronological surfaces dividing the Puesto Viejo Group into four sections (Fig. 3). The stratigraphic, sedimentological and geochemical analysis allowed to define different facies associations (Table 1), which together with the geometry of main bodies are grouped into 16 architectural elements. These elements are then described as five accumulation units (AU), which represent main depositional conditions, either under epiclastic- or volcanic-dominated sedimentation. These units were identified as: 1) debris-flow depo- sits, 2) channel-fill deposits, 3) floodplain deposits, 4) pyroclastic deposits and 5) volcanic intrusive and effusions (Figs. 4-12). The vertical and spatial distribution of volcanic and sedimentary deposits in the study area (Fig. 13) is key to understanding the evolution of Puesto Viejo Group. The lower section of the Quebradada de los Fósiles Formation started with coarse epiclastic deposits related to proximal alluvial-fan systems, located next to the border faults. These deposits were eventually covered by pyroclastic flows (Fig. 14a). Reactivation of the internal faults created structural depressions where the finer grained deposits of the upper section of the Quebradada de los Fósiles Formation was amply deposited. This section is interpreted as the development of meandering fluvial systems with low to high sinuosity that were also interrupted by the occurrence of pyroclastic flows (Fig. 14b). Subsequently, the lower section of the Río Seco de la Quebrada Formation developed from the action and/or reactivation of some internal faults. The section starts with coarse-grained deposits linked to the development of braided to meandering fluvial systems with low sinuosity and ends with lava flows (Fig. 14c). Finally, the upper section of the Río Seco de la Quebrada Formation, located in the northeastern sector of the study area, is characterized by the presence of deposits interpreted as representing the distal sectors of alluvial fans (Fig. 14d). The recorded relationships between sedimenta- tion, faulting and volcanism allow to affirm that the mechanical subsidence remained active throughout the whole history of the Puesto Viejo Group. The accommodation is concentrated in the central parts of the sub-basin. The infill evolution occurred following three successive episodes: firstly, mechanical sub- sidence; secondly, tectonic quiescence with deve- lopment of alluvial and fluvial systems; and, finally, volcanic activity (Fig. 15). This evolution controlled the development of prolonged periods of high mechanical subsidence rate together with high rate of sedimentation, alternating with short periods of time in which eruptive events were common and the rate of subsidence was comparatively low. The Puesto Viejo Group presents chronostratigra- phic, lithostratigraphic, environmental and tectonic features consistent with the rest of the Triassic sub- basins of central-western Argentina. The early stage of deposition of the Puesto Viejo Group is consistent with the early stages of syn-rift described for the Cacheuta sub-basin. The Puesto Viejo Group shows some genetic relationships with the Potrerillos and Cacheuta Formations of the Cuyo Basin, characterized by alluvial volcaniclastic deposits and meandering river systems with common development of barreales and lagoons (Kokogián and Mancilla, 1989; Kokogián et al., 2001). Contrary to this basin, however, the Puesto Viejo sub-basin lacks a post-rift stage. It is proposed here that this particular evolution could be related to its peripheral position with respect to the axis of Triassic extension, and its location on the western edge of the basin (Fig. 1a). Other sub-basins with peripheral location respect to the Triassic central basins have similar characteristics, as the Puntudo sub-basin, for example (Fig. 1a), located on the northern edge of the Cuyo Basin in the province of San Juan (Mancuso et al., 2010; Barredo, 2012). In this way, a large-scale pattern for the Triassic extension emerges during the Middle Triassic across the southwest margin of Gondwana.